Petrogenesis and geochronology of a post-orogenic calc-alkaline magmatic association: the Zulova Pluton, Bohemian Massif - Laurent,A.; Janousek,V.; Magna,T.; Schulmann,K.; Mikova,J. (Journal of Geosciences, 2014)
The Zulova Composite Pluton located at the north-eastern margin of the Bohemian Massif exposes undeformed coexisting mafic-felsic association typical of post-orogenic magmatism. The bulk of the pluton is made of biotite granite and granodiorites along with subordinate quartz monzodiorite. New LA-ICP-MS U-Pb zircon dating revealed a synchronous emplacement of the biotite granite (291 ± 5 Ma), granodiorite and quartz monzodiorite (292 ± 4 Ma). The whole-rock geochemistry and the Sr-Nd isotopic data indicate that a plausible source for the biotite granite and the granodiorite could have been a lithologically inhomogeneous pile of Devonian arc-derived, immature metagreywackes interbedded with volcaniclastics. Melting of this crustal material was probably triggered by the rise of hot basic (quartz monzodioritic) magma which could have been an enriched mantle-derived melt contaminated by the underlying Cadomian basement.The Zulova Composite Pluton is a part of a Late Carboniferous-Early Permian Sudetic Granite Belt, including in addition three large plutonic complexes distributed along major terrane boundaries: the Krkonose-Jizera, the Strzegom-Sobotka and the Strzelin massifs. The genesis of this magmatic belt was likely induced by the rise of hot mantle-derived magma in the crust while their spatially and temporally discrete emplacement at shallow levels was probably related to the (extensional) reactivation of lithospheric discontinuities at terrane boundaries. Former orogenic wedges, resulting from the inversion of youthful plate margins, represent a feasible fertile source for such post-orogenic granitoids.
Keywords: post-orogenic magmatism; geochemistry; U-Pb geochronology; Bohemian Massif; Sudetic Granite Belt